USE OF INNOVATIVE TECHNOLOGIES AS A MEANS OF FORMING COGNITIVE INTEREST TO A FOREIGN LANGUAGE - Mamirova Gulnoza, Mamirova Gulnoza (Журнал иностранных языков и лингвистики, 2021)
The article studies the problems and development of pedagogical conditions that develop cognitive interest through the use of innovative technologies in foreign language lessons.